SIMULATION OF THE TEMPERATURE PROFILE OF A PECTIN SOLUTION IN A PLATE HEAT EXCHANGER: A NON-LINEAR SYSTEM APPROACH FOR CONTROL - Scariot, M. R.; Berto, M. I.; Silveira, V. (Revista de Engenharia Térmica, 2005)
Experimental measurement can be made only of inlet and outlet global temperature of plate heat exchanger (PHE), therefore the temperature profile along of a PHE is hardly ever known. The goal of this work was to evaluate the influence of a non-Newtonian behavior of pectin solution in the temperature response curves along of the PHE. The results were obtained using a simulation codified in Matlab 6.1 software. The response curves resulted from the simulations were fitted to models for identification and characterization of the system linearity. The result shows a clear non-linear behavior of the response curves along the PHE.